The Influence of Destination Image, Attraction, and Tourist Satisfaction on Revisit Intention : Study of Kali Bening Tourists, Jepara, Indonesia - Safira, Mutiara; Komaryatin, Nurul (NUsantara Islamic Economic Journal, 2024)
This research aims to determine the influence of Destination Image, Attraction, Tourist Satisfaction on Revisit Intention. This type of research is quantitative research and uses primary data obtained from questionnaires, and secondary data obtained from the Jepara Tourism and Culture Office as well as data from the Central Statistics Agency (BPS). The sample for this research was 100 tourists who had visited the Kali Bening Tourism in Tanjung Village in 2021. The analysis used multiple linear regression analysis which was processed using SPSS version 25. The research results showed that partially the Destination Image variable had no effect, while the Attraction and Tourist Satisfaction variables had an effect on Revisit Intention at the Kali Bening Tourism Destination, Tanjung Jepara Village. Meanwhile, simultaneously, the Influence of Destination Image, Attraction, and Tourist Satisfaction on Revisit Intention at the Kali Bening Tourist Destination, Tanjung Village, Jepara Regency, Indonesia.